Debate: Stigma implications for diagnosing personality disorders in adolescents. Issue 2 (15th March 2022) - Sheehan, Lindsay; Gaurean, Beatrice; Corrigan, Patrick W.
Abstract : Diagnosing personality disorders (PDs) in adolescence is a complex and often controversial decision. While early diagnosis provides a pathway to treatment, stigmatizing labels might unintentionally increase prejudice and discrimination for youth and their families, resulting in harm and treatment avoidance. In this paper, we outline stigma‐related considerations for diagnosing PDs in adolescence, including types of stigma (public stigma, self‐stigma, associative stigma) and moderators of stigma (continuum beliefs, biogenetic attributions, PD sub‐diagnosis). Research indicates that PDs are among the most stigmatizing diagnoses in adults, particularly among healthcare providers. Experiences with stigma may differentially impact adolescents, who are undergoing rapid changes in identity development and profound influences from educational systems, peers, and social media. Youth who receive mental health services (especially those embedded in schools) worry about whether and how to talk about a diagnosis. However, adolescents with significant behavioral symptoms are often seen as different from their peers even prior to a formal diagnosis. Systematic efforts are needed to anticipate and mitigate stigma‐related impacts on adolescents who might be diagnosed with PDs.